Phenolic composition of BRS Violeta red wines produced from alternative winemaking techniques: relationship with antioxidant capacity and sensory descriptors - Machado de Castilhos, Mauricio Bonatto [UNESP]; Carvalho Tavares, Iasnaia Maria de [UNESP]; Gomez-Alonso, Sergio; Garcia-Romero, Esteban; Luiz Del Bianchi, Vanildo [UNESP]; Hermosin-Gutierrez, Isidro (Springer, 2016)
The detailed phenolic composition, sensory profile and antioxidant capacity of red wines produced from the BRS Violeta grape cultivar have been studied. The alternative winemaking procedures of grape pre-drying and submerged cap have been assessed against the traditional treatment. Malvidin was the principal anthocyanidin of BRS Violeta wines, followed by delphinidin and petunidin. It was possible to detect 17 different types of pyranoanthocyanins derived from the five anthocyanidins in their non-acylated, acylated and coumaroylated forms, being vitisin A-types and hydroxyphenyl-pyranoanthocyanins the main forms detected. Pre-dried wine presented low concentrations of anthocyanins, suggesting that they were partially degraded by the thermal treatment as a result of cleavage of covalent bounds and/or by deglycosylation of the anthocyanin 3-glucosides. Submerged cap wine presented lower anthocyanin concentration due to the limited mechanical effect caused by the constant contact between pomace and must during maceration. The 3-glucoside of the myricetin was the principal flavonol, and large amounts of coumaric and caffeic acids were observed due to the high degree of hydrolysis of their precursors, named coutaric and caftaric acids. Both alternative winemaking procedures presented no differences in the flavan-3-ol concentrations, and the antioxidant capacity of the wines did not significantly differ. The lack of differences in the main sensory descriptive attributes showed that the alternative procedures have great potential to be applied as an alternative to the traditional treatment.
Keywords: Red wine; Winemaking; Antioxidant capacity; Polyphenols; Descriptive analysis